Dilema Pendidikan dan Pendapatan di Kabupaten Grobogan - Kurniawan, Jarot (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 1, Februari 2016 (pp. 1 - 88), 2016)
Education is very important aspect in living standard improvement process.Thats believed by most of parents. Most of them have a great effort and struggle to provide a good education for their children. Article 31 UUD 1945 regulated the importance of education for the citizens of the Republic of Indonesia firmly. The government also has an obligation to provide education budget for the Indonesian people. The quetion is great sacrifice of parents and governments that provide funding for education is comparable to that expected. Based on research using two different test average with Susenas data source in 2013 showed that in Grobogan Regency, level of education have a relationship with income levels. Education is one of the variables that have relation with income level and social status level in society. This is relevant with previous studies that have been conducted by researchers and academics.
Keywords: education level; income level; relationship